2010
DOI: 10.1088/1742-6596/211/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Polarized-neutron-scattering studies on the chiral magnetism in multiferroic MnWO4

Abstract: Neutron diffraction with spherical polarization analysis is a powerful tool for studying the multiferroic materials where the ferroelectric polarization arises from a complex magnetic structure. Analyzing the off-diagonal terms in the polarization matrix one may directly detect the chiral contributions even in a multidomain arrangement. In MnWO4 one can control the chiral magnetism by varying an electric field at constant temperature. The analysis of multiferroic hysteresis cycles at four equivalent magnetic B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
(59 reference statements)
1
14
0
Order By: Relevance
“…A higher field is needed to force the sample in the notpreferred state and a lower field can reverse it into its preferred state. This is in accordance with previous results on the control of multiferroic domains by varying an electric field at constant temperature 17,27 .…”
Section: First Set Of Experiments On the In12 Spectrometersupporting
confidence: 94%
See 2 more Smart Citations
“…A higher field is needed to force the sample in the notpreferred state and a lower field can reverse it into its preferred state. This is in accordance with previous results on the control of multiferroic domains by varying an electric field at constant temperature 17,27 .…”
Section: First Set Of Experiments On the In12 Spectrometersupporting
confidence: 94%
“…Since this transition is of clear first order, one would not expect any slowing down of excitations, which could melt the pinning. Instead the lower transition is related to the anharmonic distortions of the magnetic modulation, which increase upon cooling in the multiferroic phase 27 . This increase is relatively stronger than that of the first-order magnetic modulation.…”
Section: First Set Of Experiments On the In12 Spectrometermentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, there have been only a few observations of such effects [5][6][7][8][9][10] in known multiferroic systems, and all of them can be attributed to electric field realigning ferroelectric domains and therefore causing a macroscopic magnetic response. In LuFe 2 O 4 , the ferroelectric polarization is chargevalence driven, and the charge-valence order also couples strongly to the magnetic order.…”
mentioning
confidence: 99%
“…External magnetic fields imply a flop of electric polarization, and electric fields can control chiral magnetic domains [1][2][3][4][5]. Various neutron experiments [6][7][8][9][10][11][12] as well as resonant and nonresonant x-ray studies [13,14] show that cooling in electric fields enforces a monodomain chiral state, and varying external electric fields at constant temperature drives the chiral magnetic order [9][10][11][12], which corresponds to the most promising application as a data storage medium. In addition, time resolved soft x-ray diffraction showed that chiral magnetism can be manipulated by THz-radiation pulses at an electromagnon energy [15].…”
mentioning
confidence: 99%